Política monetária no Brasil : uma análise da credibilidade do Banco Central brasileiro de 1999 A 2017 - Omurhi, Thierry Lukama (2018)
The purpose of this dissertation is to investigate the credibility of the Central Bank of Brazil (BCB) by means of transmission channels used in the economy, through the BCB monetary policy variables such as GDP, Selic, Exchange, consumer credit, credit private. To reach the goal, we analyzed the credibility indices with averages - 0.776; 0.2124; 0.6635 respectively of ICS, ICS * and ICNMB. The cointegration test, unit root and the Granger causality test were performed to estimate the VAR models of each index. It is possible to observe in the unit root test that there are 3 cases in which the indices used are stationary. The Granger Causality test presents, with a 5% significance test (from 1.96), that the ICSA credibility index has an influence on consumer credit (2.26) and on private credit (1,967), while that the ICSB index only has an influence on the exchange rate (1.98) and the ICNMB index has only an influence on the exchange rate (2,13) and the Cointegration test at the same level of significance revealed that the variables are integrated in 4 levels of integration among the 7 possible variables. The analysis of the Impulse - Response function offers in the first index the relatively positive effects / impacts for the economy as it leverages credit and the exchange rate, while the interest rate of the economy is revised downwards. In other words, the monetary policy of the Central Bank is able not only to pass tranquility by market, but also to control inflation with a sustainable economic activity in the first quarter. In the second index, the effect is negative because three of the five variables observed present results that are not adequate for the economy. The economic activity seems to be receiving and with little or almost no access to credit for investment and consumption. And finally, the third index of credibility allows to say that it exceeds the variable of the GDP, this index presents better effects in the transmission variables of monetary policy in relation to the two index because its effects have an impact in the long term.